2004
DOI: 10.2460/ajvr.2004.65.931
|View full text |Cite
|
Sign up to set email alerts
|

Comparative cardiovascular, analgesic, and sedative effects of medetomidine, medetomidine-hydromorphone, and medetomidine-butorphanol in dogs

Abstract: Medetomidine-hydromorphone or medetomidine-butorphanol is associated with improved analgesia and sedation but has cardiopulmonary effects comparable to those for medetomidine alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
62
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 24 publications
5
62
1
Order By: Relevance
“…A decrease in SV after medetomidine administration has been described in several studies (de Morais & Muir 1995;Kuo & Keegan 2004) and confirmed in this study as demonstrated by the significant difference between treatments 0 and 3 and the significant change from baseline over time in treatments 2 and 3. This decrease is most likely because of the decrease in sympathetic tone induced by medetomidine administration and not because of a direct negative inotropic effect.…”
Section: Figuresupporting
confidence: 79%
See 1 more Smart Citation
“…A decrease in SV after medetomidine administration has been described in several studies (de Morais & Muir 1995;Kuo & Keegan 2004) and confirmed in this study as demonstrated by the significant difference between treatments 0 and 3 and the significant change from baseline over time in treatments 2 and 3. This decrease is most likely because of the decrease in sympathetic tone induced by medetomidine administration and not because of a direct negative inotropic effect.…”
Section: Figuresupporting
confidence: 79%
“…Bradycardia was demonstrated in all treatments as was expected with the administration of an alpha-2 agonist (Bloor et al 1992;Flacke et al 1993;Pypendop & Verstegen 1998;Ko et al 2000;Kuusela et al 2000;Kuo & Keegan 2004;Grimm et al 2005;Pascoe 2005;Pascoe et al 2006). Medetomidine increases systemic vascular resistance, as also demonstrated in the study, and this was thought to lead to an autonomic reflex induced bradycardia (Flacke et al 1990).…”
Section: Figurementioning
confidence: 63%
“…When medetomidine was combined with hydromorphone or butorphanol, a longer duration of sedation and a better quality of analgesia was obtained than when medetomidine alone was administered in dogs (Kuo and Keegan 2004). In the current study, it can only be established that the times registered were not affected by increasing the dose of morphine from 1 mg/kg to 2 mg/kg.…”
Section: Discussionmentioning
confidence: 99%
“…The potent sedation created by medetomidine and dexmedetomidine exhibit a dose dependent duration [5]. Sedation lasting up to 240 min has been reported [4–6, 28, 29]. This makes a strong argument for pharmacological antagonism of medetomidine or dexmedetomidine with atipamezole once the procedure is completed.…”
Section: Discussionmentioning
confidence: 99%